Finite Element Simulation of the Local Al/Si Contact Formation. (August 2016) - Herguth, Axel
Abstract: The formation of local Al/Si contacts, as found in PERC type cells, was evaluated by finite element simulation based on a model of Si diffusion in the molten Al layer as well as dissolution and recrystallization of Si at the liquid/solid interface. In accordance with experimental observations the simulations reproduce the characteristic lateral spread of Si in the Al layer, the different cavity shapes (ranging from round to ω-shaped cavities) as well as the development of the Al-doped recrystallized region which forms the high-low junction to the lower doped substrate responsible for the back surface field passivation.